Targeting TL1A/DR3 Signaling Offers a Therapeutic Advantage to Neutralizing IL13/IL4Rα in Muco-Secretory Fibrotic Disorders - Steele, Hope; Sachen, Kacey; McKnight, Andrew J.; Soloff, Rachel; Herro, Rana (Frontiers in Immunology, 2021)
Mucus hypersecretory disorders including asthma, chronic obstructive pulmonary disease (COPD) and cystic fibrosis exhibit increased morbidity. Current therapeutic interventions include administration of mucolytics and anti-inflammatory drugs; there remains a need for therapies with greater effectiveness and durability. We demonstrate that the TNF superfamily member 15 (aka TL1A), administered in isolation in the airways, induces mucus production in the lungs by bronchial goblet cells. We present evidence that the muco-secretory activity of TL1A is dependent on IL13. Furthermore, we show TL1A induces IL13 expression by innate lymphoid cells leading to mucus production. Blocking TL1A post-disease onset, in a murine model of asthma induced by chronic exposure to house dust mite, diminishes mucus production. Targeting TL1A offers a promising therapeutic benefit to muco-secretory disorders in addition to airway inflammation and fibrosis.